Collapse period of degrading SDOF systems - Borekci, M.; Kircil, M. S.; Ekiz, I (SPRINGER, 2014)
Seismic demand estimation for a structure is a critical issue for seismic performance assessment so that the potential damage can be estimated realistically. Many researchers proposed simplified methods to estimate the demand of a structure under strong ground motions. However, most of them did not consider degradation and collapse potential of the structures. Even some of theme considered the degradation effect, stiffness and strength degradation effects were considered separately without collapse potential caused by dynamic instability. In this study, collapse potential of SDOF systems caused by dynamic instability with stiffness and strength degradation has been investigated. Nonlinear time history analyses were performed, using an energy-based, strength and stiffness degraded hysteretic model that considers the collapse potential, with 160 earthquake acceleration time histories. An equation was proposed for the estimation of collapse period of SDOF systems as a function of certain strength reduction factor, ductility level and post-capping stiffness ratio. Finally, effects of parameters of the considered hysteretic model and local site conditions on the collapse period were investigated.
Keywords: collapse; degradation; dynamic instability; hysteretic types; earthquake; INELASTIC DISPLACEMENT RATIOS; SIMPLE STRUCTURAL SYSTEMS; SEISMIC DESIGN; INSTABILITY; BUILDINGS; CAPACITY; SPECTRA; SITES; Engineering